2018
DOI: 10.1177/0095798418811476
|View full text |Cite
|
Sign up to set email alerts
|

Helplessness Mediates Racial Discrimination and Depression for African American Young Adults

Abstract: Racial discrimination is associated with depressive symptoms for young African American adults. Yet few studies have examined the psychological mechanisms for this association. The purpose of this preliminary study was to examine the mediating effect of helplessness on the association between perceived racial discrimination and depressive symptoms in a sample of 172 African American young adults. Measures of perceived racial discrimination, depression, and helplessness were administered. Though the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 59 publications
3
15
0
Order By: Relevance
“…Furthermore, the complementary logistic regression analyses showed that those with the highest level of everyday racial discrimination were more than 36 times more likely to have significant symptoms of depression compared to those with a lower level of everyday racial discrimination. These analyses corroborate several decades of research, particularly in the United States, which have shown that everyday racial discrimination is associated with a variety of mental health problems, including depression (Brooks et al, 2020; Hudson et al, 2012, 2015; Madubata et al, 2018; Walker et al, 2014; Williams & Mohammed, 2013; Williams & Williams‐Morris, 2000). The results of this study are particularly interesting because, compared to the racial context in the United States, Canada often takes a colorblind approach across health and education sectors that typically ignores the major consequences of racism.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Furthermore, the complementary logistic regression analyses showed that those with the highest level of everyday racial discrimination were more than 36 times more likely to have significant symptoms of depression compared to those with a lower level of everyday racial discrimination. These analyses corroborate several decades of research, particularly in the United States, which have shown that everyday racial discrimination is associated with a variety of mental health problems, including depression (Brooks et al, 2020; Hudson et al, 2012, 2015; Madubata et al, 2018; Walker et al, 2014; Williams & Mohammed, 2013; Williams & Williams‐Morris, 2000). The results of this study are particularly interesting because, compared to the racial context in the United States, Canada often takes a colorblind approach across health and education sectors that typically ignores the major consequences of racism.…”
Section: Discussionsupporting
confidence: 73%
“…A recent study comparing postsecondary students found the prevalence of depression to be 9.85% among non-Indigenous students and 14.12% among Indigenous students in the past 12 months (Hop Wo et al, 2020). Another study conducted with a very large sample of Indigenous people revealed a prevalence of 11.65% (Elamoshy et al, 2018 (Madubata et al, 2018). The present study also showed that women, people with less than a postsecondary education, married people, employed people, people 25 years of age and older, and people born in Canada have higher prevalence of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations